A comunicação na relação de serviço : um estudo exploratório - Santos, Marcos Ferreira (2005)
This dissertation is an exploratory study on the importance of communication in the service relationship. It’s central objective is to investigate the influence of communication on the service relationship, been that the moment in which the service is pro